Symposium 6: Democratic Collaborative Dialogue and Negotiation of Meaning in Digital Teaching and Learning Environments: Reflections - Sorensen, Elsebeth Korsgaard (Proceedings of the International Conference on Networked Learning, 2010)
This paper explores, from a theoretical perspective, the methodological potential of digital democratic dialogue as a vehicle for enhancing intercultural collaborative education in networked learning environments. It examines the dialogical approach to design, which has been practiced, developed and unfolding within parts of MIL (Master programme in ICT and Learning) throughout the last 10 years, guided by a design based research perspective. Theoretically, among other theoretical positions, the paper draws on Wittgenstein’s notion of ‘language games’. The paper makes a plea for the notion of language games as a means of identifying the smallest analytical unit of democratic dialogues in digital negotiation of meaning. Enhancement of dialogic quality in computer supported collaborative learning processes on the Web appears a broad, complex and multi-faced challenge. The central challenge is to identify and employ aspects of instructional design that stimulate and support the evolution of collaborative democratic dialogue in digital environments. A related challenge is the task of choosing criteria for the evaluation/assessment of these processes. Addressing these issues usually involves establishing balanced design criteria in the instructional marriage between technology and pedagogy. It also presumes a rooting in a set of values as well as an ethical dimension concerning inter human and intercultural co-existence. If we think beyond simply creating an online mechanism for dialog to creating a framework that will promote high-quality interaction and allow for relevant evaluation/assessment, we must search for the appropriate, educating analytical unit. In order to do so, I need to start from a clarification of the learning perspective behind the design and construct the analytical unit from this perspective. Departing from previous research, the paper presents a theoretically based conceptual framework based on the notion of “collaborative learning in online communities of practice” (Dillenbourg et al., 1995; Harasim, 1995; Koschmann, 1994; Wenger, 1998) for understanding and identifying collaborative knowledge building dialogue for democratic citizenship. This includes identification of an alternative analytical and evaluative unit in distributed collaborative knowledge building on the Web, inspired by the concept of “language games” (Wittgenstein, 1974). I also discuss implications of this for design learning processes that allow students to collaboratively develop “knowledge tapestries” through meta-awareness of how such language game structure is developed. The paper builds on previous reports on collaborative knowledge building (e.g. Sorensen and Takle, 2001).